Method for producing recycled acrylic pressure-sensitive adhesive and recycled acrylic pressure-sensitive adhesive tape

By reacting acrylic adhesives with specific liquids and alkaline compounds to create reused acrylic polymers, it solves the problem of unenvironmentally friendly waste disposal of adhesive tapes and achieves efficient regeneration and reuse of adhesives.

CN119343422APending Publication Date: 2025-01-21NITTO DENKO CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046172.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-04-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reuse acrylic adhesives, resulting in the waste treatment of adhesive tapes being unecotically friendly.

Method used

A hydrophilic polymer is produced by reacting an acrylic adhesive with a liquid and an alkaline compound having a Hansen solubility parameter value of 31 or less, and reacts with alcohols to produce a recycled acrylic polymer.

Benefits of technology

Regeneration and reuse of acrylic adhesives are realized, reducing the environmental load of adhesive tape waste and reducing the consumption of fossil resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179741430000211
    Figure BDA0005179741430000211
  • Figure BDA0005179741430000301
    Figure BDA0005179741430000301
Patent Text Reader

Abstract

Provided is a method for producing a recycled acrylic adhesive by regenerating a base polymer from an acrylic adhesive. Also provided is a recycled acrylic pressure-sensitive adhesive tape using the recycled acrylic pressure-sensitive adhesive obtained by the production method. A method for producing a recycled acrylic adhesive according to an embodiment of the present invention comprises: a step (I) for producing a hydrophilic polymer by reacting an acrylic adhesive with a liquid having a Hansen solubility parameter value of 31 or less and a basic compound; and a step (II) for producing a recycled acrylic polymer by reacting the hydrophilic polymer with an alcohol (A2).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a recycled acrylic adhesive and a recycled acrylic adhesive tape. Background Art

[0002] Adhesive tapes are widely used for attaching labels to articles, packaging materials, packing packaging materials, applications in the manufacturing process of electronic components and optical components, masking purposes, etc. In recent years, in particular, the application of adhesive tapes in the manufacturing process of electronic components and optical components has increased, and a large amount of adhesive tape waste is generated at manufacturing sites, etc.

[0003] The waste of the adhesive tape is usually disposed of by burning or taken to a waste disposal site for disposal. However, such disposal is not preferred from the viewpoint of reducing environmental load and further from the viewpoint of resource recycling.

[0004] Therefore, it is necessary to reduce the above-mentioned waste disposal of adhesive tape as much as possible and reuse resources. As a means to reduce the waste disposal of such adhesive tape, the recycling of adhesive tape raw materials is considered. If the recycling technology of adhesive tape raw materials is established, it is related to, for example, suppressing the CO2 emission caused by fossil resource mining, and is expected to have a great effect even in the face of solving the problem of climate change.

[0005] As raw materials of the adhesive tape, adhesives and substrates can be representatively cited. The adhesive tape is typically obtained by dissolving a base polymer and additives such as a crosslinking agent that meet the purpose in a solvent to form an adhesive composition, applying the composition to a substrate, and performing heating / drying as needed to allow a crosslinking reaction to proceed, thereby forming an adhesive on the substrate (e.g., Patent Document 1).

[0006] As mentioned above, the typical adhesive used as the raw material of the adhesive tape has a cross-linked structure formed by a cross-linking reaction and is not easily soluble in a solvent, so it cannot be directly treated as a recycled adhesive composition applied to a substrate. Therefore, in order to reuse such an adhesive, the cross-linked structure in the adhesive must be cut and regenerated as a base polymer.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-175796 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] The present invention aims to provide a method for producing a recycled acrylic adhesive by regenerating a base polymer from an acrylic adhesive, and to provide a recycled acrylic adhesive tape using the recycled acrylic adhesive obtained by the production method.

[0012] Solutions for solving problems

[0013] [1] The method for producing a recycled acrylic adhesive according to an embodiment of the present invention comprises the following steps: step (I), reacting an acrylic adhesive with a liquid having a Hansen solubility parameter value of 31 or less and an alkaline compound to produce a hydrophilic polymer; and step (II), reacting the hydrophilic polymer with an alcohol (A2) to produce a recycled acrylic polymer.

[0014] [2] In the method for producing a recycled acrylic adhesive described in [1] above, the liquid having a Hansen solubility parameter value of 31 or less may contain at least one selected from the group consisting of alcohols (A1), hydrocarbons, ketones, esters, ethers, amines, nitriles, carboxylic acids and terpenes.

[0015] [3] In the method for producing a recycled acrylic adhesive described in [2] above, the liquid having a Hansen solubility parameter value of 31 or less may necessarily contain the alcohol (A1).

[0016] [4] In the method for producing a recycled acrylic adhesive according to [2] or [3], the alcohol (A1) may contain an alcohol having 1 to 8 carbon atoms.

[0017] [5] In the method for producing a recycled acrylic adhesive as described in any one of [2] to [4], the acrylic adhesive has -COO-R 1 The structure of the alcohol (A1) is R 21 -OH, the R 1 With the R 21 Can be the same.

[0018] [6] In the method for producing a recycled acrylic adhesive as described in any one of [2] to [4], the acrylic adhesive has -COO-R 1 The structure of the alcohol (A1) is R 21 -OH, the R 1 With the R 21 Can be different.

[0019] [7] In the method for producing a recycled acrylic adhesive as described in any one of [1] to [6], the acrylic adhesive has -COO-R 1 The alcohol (A2) has a structure of R 22 -OH, the R1 With the R 22 Can be the same.

[0020] [8] In the method for producing a recycled acrylic adhesive as described in any one of [1] to [6], the acrylic adhesive has -COO-R 1 The alcohol (A2) has a structure of R 22 -OH, the R 1 With the R 22 Can be different.

[0021] [9] The method for producing a recycled acrylic adhesive according to any one of [1] to [8] above may include the step (III) of separating the acrylic adhesive from the adhesive tape having the acrylic adhesive.

[0022]

[10] The method for producing a recycled acrylic pressure-sensitive adhesive according to any one of [1] to [9] above may include the step (IV) of reacting the recycled acrylic polymer with a cross-linking agent.

[0023]

[11] A recycled acrylic pressure-sensitive adhesive tape according to an embodiment of the present invention includes a recycled acrylic pressure-sensitive adhesive obtained by the method for producing a recycled acrylic pressure-sensitive adhesive according to any one of [1] to

[10] above and a substrate.

[0024] Effects of the Invention

[0025] According to the present invention, there can be provided a method for producing a recycled acrylic adhesive by regenerating a base polymer from an acrylic adhesive, and a recycled acrylic adhesive tape using the recycled acrylic adhesive obtained by the production method. DETAILED DESCRIPTION

[0026] When "weight" is used in this specification, it can be read as "mass" which is a commonly used SI unit for expressing weight.

[0027] In this specification, when “(meth)acrylic acid” is used, it means “acrylic acid and / or methacrylic acid”, when “(meth)acrylate” is used, it means “acrylate and / or methacrylate”, when “(meth)allyl” is used, it means “allyl and / or methallyl”, and when “(meth)acrolein is used, it means “acrolein and / or methacrolein”.

[0028] <<<<1. Method for producing recycled acrylic adhesive>>>>

[0029] The method for producing a recycled acrylic adhesive according to an embodiment of the present invention comprises the following steps: step (I), reacting an acrylic adhesive with a liquid having a Hansen solubility parameter value of 31 or less and an alkaline compound to produce a hydrophilic polymer; and step (II), reacting the hydrophilic polymer with an alcohol (A2) to produce a recycled acrylic polymer.

[0030] The method for producing a recycled acrylic adhesive according to an embodiment of the present invention may include step (III) of separating the acrylic adhesive from the adhesive tape having the acrylic adhesive. Typically, step (III) may be included before step (I).

[0031] The recycled acrylic polymer obtained in step (II) may be used as a recycled acrylic adhesive directly, or may be reacted with a crosslinking agent to form a recycled acrylic adhesive having a crosslinked structure. That is, the method for producing a recycled acrylic adhesive according to an embodiment of the present invention may include the following step (IV): reacting the recycled acrylic polymer obtained in step (II) with a crosslinking agent. Preferably, step (IV) may be included after step (II).

[0032] The method for producing a recycled acrylic pressure-sensitive adhesive according to an embodiment of the present invention may include any appropriate other steps within the range that does not impair the effects of the present invention. The other steps may be only one or two or more.

[0033] <<1-1. Step (I)>>

[0034] Step (I) is a step of reacting an acrylic adhesive, a liquid having a Hansen solubility parameter value of 31 or less, and a basic compound to produce a hydrophilic polymer.

[0035] In step (I), as a method for reacting an acrylic adhesive with a liquid having a Hansen solubility parameter value of less than 31 and an alkaline compound, any appropriate method can be adopted within the scope that does not impair the effect of the present invention. As such a method, in terms of being able to further reflect the effect of the present invention, the following method can be preferably cited: impregnating an acrylic adhesive with an adhesive treatment liquid containing a liquid having a Hansen solubility parameter value of less than 31 and an alkaline compound. As a method for such impregnation, any appropriate impregnation method can be adopted within the scope that does not impair the effect of the present invention, depending on the scale, the type of acrylic adhesive, etc. It should be noted that in this specification, "impregnating the acrylic adhesive with the adhesive treatment liquid" means a state in which the adhesive treatment liquid is impregnated with the acrylic adhesive, for example, a state in which at least a portion of the acrylic adhesive is immersed in the adhesive treatment liquid can be cited. This is because, if at least a portion of the acrylic adhesive is immersed in the adhesive treatment liquid, the adhesive treatment liquid gradually penetrates into the acrylic adhesive.

[0036] A preferred embodiment of step (I) is as follows: stirring is performed in a state where the acrylic adhesive is impregnated with the adhesive treatment liquid. By stirring in a state where the acrylic adhesive is impregnated with the adhesive treatment liquid, a hydrophilic polymer can be produced more smoothly from the acrylic adhesive. It should be noted that in this specification, "a state where the acrylic adhesive is impregnated with the adhesive treatment liquid" means a state where the adhesive treatment liquid is impregnated with the acrylic adhesive, and for example, the following state can be cited: at least a portion of the acrylic adhesive is impregnated with the adhesive treatment liquid. This is because, if at least a portion of the acrylic adhesive is impregnated with the adhesive treatment liquid, the adhesive treatment liquid gradually penetrates into the acrylic adhesive.

[0037] The usage ratio of the acrylic adhesive and the adhesive treatment liquid can be any appropriate usage ratio within the range that does not impair the effects of the present invention, depending on the type of acrylic adhesive to be used, the type of adhesive treatment liquid, etc. Such usage ratio is, for example, preferably 1:0.5 to 1:50, more preferably 1:1 to 1:30, further preferably 1:3 to 1:20, and particularly preferably 1:5 to 1:10 in terms of weight ratio.

[0038] As a stirring method, any appropriate stirring method can be adopted within the range that does not impair the effect of the present invention according to the scale, the type of acrylic adhesive, etc. As for the stirring time, any appropriate stirring time can be adopted within the range that does not impair the effect of the present invention according to the scale, the type of acrylic adhesive, etc.

[0039] A preferred embodiment of step (I) is as follows: ultrasonic treatment is performed in a state where the acrylic adhesive is impregnated with the adhesive treatment liquid. By performing ultrasonic treatment in a state where the acrylic adhesive is impregnated with the adhesive treatment liquid, a hydrophilic polymer can be produced more smoothly from the acrylic adhesive.

[0040] As the method of ultrasonic treatment, any appropriate ultrasonic treatment method can be adopted according to the scale, the type of acrylic adhesive, etc., within the range not impairing the effects of the present invention.

[0041] The temperature of the acrylic adhesive in the state of being impregnated with the adhesive treatment liquid is preferably 10° C. or higher, more preferably 15° C. or higher, more preferably 20° C. or higher, more preferably 25° C. or higher, more preferably 30° C. or higher, and particularly preferably 35° C. or higher in order to further exhibit the effects of the present invention, and the upper limit is preferably 120° C. or lower, more preferably 100° C. or lower, and further preferably 80° C. or lower. When the temperature of the acrylic adhesive in the state of being impregnated with the adhesive treatment liquid is within the above range, a hydrophilic polymer can be produced smoothly and simply from the acrylic adhesive under mild conditions.

[0042] It is speculated that according to step (I), the acrylic adhesive is swollen by the adhesive treatment liquid, and is hydrolyzed by the liquid having a Hansen solubility parameter value of 31 or less and the alkaline compound contained in the adhesive treatment liquid (including a saponification reaction of generating salts and alcohols by the reaction of esters and bases). As a result, a hydrophilic polymer derived from the acrylic adhesive is formed. Here, the "hydrophilic polymer derived from the acrylic adhesive" refers to a hydrophilic polymer having a structure derived from a base polymer used in the formation of the acrylic adhesive, and specifically, for example, refers to a hydrophilic polymer having a structure in which at least a part of the functional groups (such as carboxyl groups and ester groups) present at the side chain ends of the base polymer constituting the acrylic adhesive is hydrolyzed by the liquid having a Hansen solubility parameter value of 31 or less and the alkaline compound contained in the adhesive treatment liquid (including a saponification reaction of generating salts and alcohols by the reaction of esters and bases).

[0043] The formed hydrophilic polymer may be further treated with a solvent as needed to form a solution or dispersion. For example, a solution in which the hydrophilic polymer is dissolved in an aqueous solvent may be formed. Examples of the aqueous solvent include water, alcohol, mixed solvents thereof, and mixed solvents of these with an organic solvent.

[0044] The weight average molecular weight of the hydrophilic polymer obtained in step (I) is preferably 100,000 to 3,000,000, more preferably 150,000 to 2,000,000, further preferably 200,000 to 1,500,000, and particularly preferably 250,000 to 1,000,000.

[0045] The Tg (glass transition temperature) of the hydrophilic polymer obtained in step (I) is preferably 50°C to 150°C, more preferably 70°C to 140°C, further preferably 80°C to 130°C, particularly preferably 90°C to 120°C.

[0046] According to step (I), a hydrophilic polymer can be easily obtained from an acrylic adhesive under mild conditions. This is presumably because, according to step (I), hydrolysis of the acrylic adhesive (including saponification reaction to generate a salt and an alcohol by reaction of an ester with a base) is easily performed under mild conditions, and as a result, a hydrophilic polymer is obtained.

[0047] Conventionally, in order to carry out the hydrolysis of acrylic adhesives (including saponification reaction of producing salts and alcohols by reaction of esters and bases), it is necessary to make the acrylic adhesives carry out the above reaction under conditions of high temperature and high pressure, or to design the composition of the acrylic adhesives to a limited composition. According to step (I), it is possible to carry out good hydrolysis of acrylic adhesives (including saponification reaction of producing salts and alcohols by reaction of esters and bases) simply under mild conditions without forming conditions of high temperature and high pressure and without designing the composition of the acrylic adhesives to a limited composition.

[0048] <1-1-a. Acrylic adhesive>

[0049] Any appropriate acrylic adhesive can be used as the acrylic adhesive within the range that does not impair the effect of the present invention. As such acrylic adhesive, a typical example is an acrylic adhesive that is a waste (sometimes referred to as "waste acrylic adhesive"). Examples of the waste acrylic adhesive include: an acrylic adhesive contained in an acrylic adhesive tape that is recycled after use, an acrylic adhesive that has residual adhesive on an adherend when the acrylic adhesive tape is peeled off from an adherend to which the acrylic adhesive tape is adhered, and an acrylic adhesive attached to an acrylic adhesive manufacturing device.

[0050] The acrylic adhesive is in the form of an adhesive layer contained in an acrylic adhesive tape, in the form of an adhesive with adhesive residue on an adherend, or in the form of an adhesive attached to a manufacturing device such as a polymerization reactor, a compounding device, or a coater, and therefore has various sizes and forms.

[0051] Acrylic adhesive can be formed according to any appropriate method. As such a method, for example, a method formed by an acrylic adhesive composition can be cited, and more specifically, the following method can be cited: the acrylic adhesive composition is coated on any appropriate substrate, heated / dried as required, and cured as required to form an adhesive (specifically, an adhesive layer) on the substrate. As such a coating method, for example, methods such as a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a rod coater, a blade coater, an air knife coater, a spray coater, a comma coater, a direct coater, a roller brush coater, and a die coater can be cited.

[0052] In order to further exhibit the effects of the present invention, the acrylic pressure-sensitive adhesive composition preferably includes an acrylic polymer and a cross-linking agent.

[0053] The acrylic polymer can be referred to as a base polymer in the field of acrylic pressure-sensitive adhesives. The acrylic polymer may be one type or two or more types.

[0054] The content of the acrylic polymer in the acrylic pressure-sensitive adhesive composition is preferably 50 to 100 wt %, more preferably 60 to 100 wt %, further preferably 70 to 100 wt %, particularly preferably 80 to 100 wt %, and most preferably 90 to 100 wt %, calculated on a solid basis.

[0055] As the acrylic polymer, any appropriate acrylic polymer can be adopted within a range not impairing the effects of the present invention.

[0056] The weight average molecular weight of the acrylic polymer is preferably 100,000 to 3,000,000, more preferably 150,000 to 2,000,000, further preferably 200,000 to 1,500,000, particularly preferably 250,000 to 1,000,000.

[0057] The Tg (glass transition temperature) of the acrylic polymer is preferably -100°C to 30°C, more preferably -95°C to 20°C, further preferably -90°C to 10°C, particularly preferably -80°C to 0°C.

[0058] In order to further demonstrate the effects of the present invention, the acrylic polymer is preferably an acrylic polymer obtained by polymerizing a composition (A) comprising (component a) an alkyl (meth)acrylate having 4 to 12 carbon atoms in the alkyl group of the alkyl ester moiety and (component b) at least one selected from the group consisting of (meth)acrylate having an OH group and (meth)acrylic acid. (component a) and (component b) may each independently be one or more.

[0059] Examples of the alkyl (meth)acrylate (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms include n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are more preferred in terms of further exhibiting the effects of the present invention.

[0060] As at least one (component b) selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid, for example, (meth)acrylates having an OH group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, (meth)acrylic acid, etc., are mentioned. Among these, hydroxyethyl (meth)acrylate and (meth)acrylic acid are preferred, and hydroxyethyl acrylate and acrylic acid are more preferred in terms of further exhibiting the effects of the present invention.

[0061] The composition (A) may contain a copolymerizable monomer other than the components (a) and (b). The copolymerizable monomer may be one kind or two or more kinds. Examples of such copolymerizable monomers include: carboxyl group-containing monomers such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their anhydrides (e.g., anhydride group-containing monomers such as maleic anhydride and itaconic anhydride) (excluding (meth)acrylic acid); amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide; amino group-containing monomers such as aminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, and tert-butylaminoethyl(meth)acrylate; epoxy group-containing monomers such as glycidyl(meth)acrylate and methylglycidyl(meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, N-vinylpiperidone, N-vinyl Heterocyclic vinyl monomers such as 1-aminopiperazine, N-vinylpyrrole, N-vinylimidazole, vinylpyridine, vinylpyrimidine, and vinyloxazole; sulfonic acid group-containing monomers such as sodium vinyl sulfonate; phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate; imide group-containing monomers such as cyclohexylmaleimide and isopropylmaleimide; isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate; (meth)acrylates having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylates having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ether; vinyl chloride; etc.

[0062] As copolymerizable monomers, multifunctional monomers can also be used. Multifunctional monomers refer to monomers having two or more ethylenically unsaturated groups in one molecule. As ethylenically unsaturated groups, any appropriate ethylenically unsaturated groups can be used within the scope that does not impair the effect of the present invention. As such ethylenically unsaturated groups, for example, free radical polymerizable functional groups such as vinyl, propenyl, isopropenyl, vinyl ether (vinyloxy), and allyl ether (allyloxy) can be cited. Examples of the multifunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. Such a multifunctional monomer may be one or more.

[0063] As the copolymerizable monomer, an alkoxyalkyl (meth)acrylate can also be used. Examples of the alkoxyalkyl (meth)acrylate include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The alkoxyalkyl (meth)acrylate may be one or more.

[0064] The content of the alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms (component a) in the alkyl ester moiety is preferably 50% by weight or more, more preferably 60% to 100% by weight, further preferably 70% to 100% by weight, and particularly preferably 80% to 100% by weight, based on the total amount of monomer components constituting the acrylic polymer (100% by weight), in order to further exhibit the effects of the present invention.

[0065] The content of at least one (component b) selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid is preferably 0.1% by weight or more, more preferably 1.0% by weight to 50% by weight, further preferably 1.5% by weight to 40% by weight, and particularly preferably 2.0% by weight to 30% by weight, based on the total amount (100% by weight) of the monomer components constituting the acrylic polymer, in order to further exhibit the effects of the present invention.

[0066] In the acrylic polymer, the total amount of the above-mentioned (a component), the above-mentioned (b component) and the carboxyl group-containing monomer is preferably 5% to 95% by weight, more preferably 10% to 95% by weight, further preferably 15% to 95% by weight, further preferably 20% to 95% by weight, further preferably 25% to 95% by weight, further preferably 30% to 95% by weight, particularly preferably 35% to 90% by weight, and most preferably 40% to 90% by weight, relative to the total amount of monomer components (100% by weight).

[0067] Composition (A) can contain any appropriate other components within the scope that does not damage the effect of the present invention. As such other components, for example, polymerization initiator, chain transfer agent, solvent etc. can be cited. The content of these other components can adopt any appropriate content within the scope that does not damage the effect of the present invention.

[0068] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), etc., depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.

[0069] The thermal polymerization initiator can be used when the acrylic polymer is obtained by solution polymerization. As such a thermal polymerization initiator, for example, an azo polymerization initiator, a peroxide polymerization initiator (for example, dibenzoyl peroxide, tert-butyl permaleate, etc.), a redox polymerization initiator, etc. can be mentioned. Among these thermal polymerization initiators, the azo initiator disclosed in Japanese Patent Publication No. 2002-69411 is particularly preferred. In terms of the fact that the decomposition product of the polymerization initiator is not easy to remain in the acrylic polymer as a part that causes the generation of gas (exhaust) generated by heating, such an azo polymerization initiator is preferred. As an azo polymerization initiator, 2,2'-azobisisobutyronitrile (hereinafter, sometimes referred to as AIBN), 2,2'-azobis-2-methylbutyronitrile (hereinafter, sometimes referred to as AMBN), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, etc. can be mentioned. The amount of the azo polymerization initiator used is preferably 0.01 to 5.0 parts by weight, more preferably 0.05 to 4.0 parts by weight, further preferably 0.1 to 3.0 parts by weight, particularly preferably 0.15 to 3.0 parts by weight, and most preferably 0.20 to 2.0 parts by weight, based on the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.

[0070] The photopolymerization initiator is preferably used when obtaining an acrylic polymer by active energy ray polymerization. Examples of the photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.

[0071] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. can be mentioned. As benzoin-based photopolymerization initiators, for example, benzoin, etc. can be mentioned. As benzyl-based photopolymerization initiators, for example, benzyl, etc. can be mentioned. As benzophenone-based photopolymerization initiators, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be mentioned. As ketal-based photopolymerization initiators, for example, benzyldimethylketal, etc. can be mentioned. As thioxanthone-based photopolymerization initiators, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. can be mentioned.

[0072] The amount of the photopolymerization initiator used is preferably 0.01 to 3.0 parts by weight, more preferably 0.015 to 2.0 parts by weight, further preferably 0.02 to 1.5 parts by weight, particularly preferably 0.025 to 1.0 parts by weight, and most preferably 0.03 to 0.50 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.

[0073] The acrylic adhesive composition may contain a crosslinking agent. By using a crosslinking agent, the cohesive force of the acrylic adhesive can be improved, and the effect of the present invention can be further manifested. The crosslinking agent may be only one kind or two or more kinds.

[0074] As the crosslinking agent, in addition to polyfunctional isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, and peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. can also be mentioned. Among these, in terms of further demonstrating the effect of the present invention, at least one (component c) selected from the group consisting of polyfunctional isocyanate crosslinking agents and epoxy crosslinking agents is preferred.

[0075] Examples of the polyfunctional isocyanate crosslinking agent include: lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylene diisocyanate, and polymethylene polyphenyl polyisocyanate; trimethylolpropane / toluene diisocyanate adducts (e.g., Coronate L manufactured by Nippon Polyurethane Industry Co., Ltd. or Tosoh Corporation, Takenate 1 manufactured by Mitsui Chemicals, Inc. Isocyanate adducts such as trimethylolpropane / hexamethylene diisocyanate adduct (e.g., trade name “Takenate D101E” manufactured by Nippon Polyurethane Industry Co., Ltd. or Tosoh Corporation), isocyanurate of hexamethylene diisocyanate (e.g., trade name “Coronate HX” manufactured by Nippon Polyurethane Industry Co., Ltd. or Tosoh Corporation); trimethylolpropane / xylene diisocyanate adduct (e.g., trade name “Takenate D110N” manufactured by Mitsui Chemicals, Inc., trade name “Takenate D120N” manufactured by Mitsui Chemicals, Inc.), trimethylolpropane / isophorone diisocyanate adduct (e.g., trade name “Takenate D140N” manufactured by Mitsui Chemicals, Inc.), trimethylolpropane / hexamethylene diisocyanate adduct (e.g., trade name “Takenate D160N” manufactured by Mitsui Chemicals, Inc.), and isocyanurate of hexamethylene diisocyanate (e.g., trade name “Takenate D170N” manufactured by Mitsui Chemicals, Inc.). D160N”); polyether polyisocyanate, polyester polyisocyanate, and adducts thereof with various polyols; polyisocyanates multifunctionalized with isocyanurate bonds, biuret bonds, allophanate bonds, etc.

[0076] As the epoxy crosslinking agent (polyfunctional epoxy compound), a polyfunctional epoxy compound having two or more epoxy groups in one molecule can be used. As the epoxy crosslinking agent, for example, N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol In addition to oil polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl isocyanurate-tri(2-hydroxyethyl)ester, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, etc. As epoxy crosslinking agents, commercial products such as trade names "TETRAD C" and "TETRAD X" (manufactured by Mitsubishi Gas Chemical Co., Ltd.) can also be mentioned.

[0077] The content of the crosslinking agent in the acrylic adhesive composition can be any appropriate content within the range that does not impair the effect of the present invention. As such a content, for example, in order to further demonstrate the effect of the present invention, it is preferably 0.1 to 5.0 parts by weight, more preferably 0.2 to 4.5 parts by weight, further preferably 0.3 to 4.0 parts by weight, and particularly preferably 0.4 to 3.5 parts by weight relative to the solid content (100 parts by weight) of the acrylic polymer.

[0078] The acrylic adhesive composition may contain any other appropriate components within the scope that does not impair the effect of the present invention. Such other components include, for example, polymer components other than acrylic polymers, crosslinking accelerators, crosslinking catalysts, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, preservatives, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.

[0079] <1-1-b. Adhesive treatment liquid>

[0080] The adhesive treatment liquid includes a liquid having a Hansen solubility parameter value of 31 or less and an alkaline compound.

[0081] The term "liquid" as used herein refers to liquid at normal temperature and pressure, and common examples thereof include water, alcohol, and other various solvents.

[0082] The liquids having a Hansen solubility parameter value of 31 or less may be only one type or two or more types.

[0083] The "Hansen solubility parameter value" is the Hildebrand solubility parameter value divided into dispersion terms (δ D ), polar term (δ p ) and hydrogen bonding terms (δ H ) These three components take into account the parameter values ​​of the polarity of the substance, sometimes referred to as HSP values. Dispersion terms (terms involving van der Waals forces), polar terms (terms involving dipole moments) and hydrogen bonding terms (terms involving hydrogen bonds) can be expressed in three-dimensional coordinates.

[0084] The Hansen solubility parameter value of a mixed solution of two or more liquids can be calculated as the weighted average value m of the HSP values ​​of each solvent according to the following formula (1). It should be noted that δ1 and δ2 are the HSP values ​​of each liquid component, and is the volume fraction of each liquid component.

[0085]

[0086] The Hansen solubility parameter values ​​of each solvent are listed in "HSPiP ver.5", and for solvents not listed, values ​​estimated from "HSPiP ver.5" were used.

[0087] The Hansen solubility parameter value of the liquid is 31 or less, preferably 30 or less, more preferably 29 or less, further preferably 28 or less, and particularly preferably 25 or less. The lower limit of the Hansen solubility parameter value of the liquid is preferably 7 or more, more preferably 10 or more, further preferably 13 or more, and particularly preferably 15 or more. When the Hansen solubility parameter value of the liquid is within the above range, preferably 10 or more and 30 or less, and more preferably 15 or more and 25 or less, a hydrophilic polymer can be efficiently produced from an acrylic adhesive.

[0088] If the Hansen solubility parameter value of the liquid exceeds 31, there is a concern that, for example, the permeability of the adhesive treatment liquid to the acrylic adhesive may deteriorate, and there is a concern that the production efficiency of the hydrophilic polymer may decrease. If the Hansen solubility parameter value of the liquid becomes less than 7, although it is not as different from the case where the Hansen solubility parameter value exceeds 31, there is a concern that, for example, the permeability of the adhesive treatment liquid to the acrylic adhesive may deteriorate, and there is a concern that the production efficiency of the hydrophilic polymer may decrease.

[0089] As for the liquid having a Hansen solubility parameter value of 31 or less, the following liquids can be representatively mentioned as a single liquid. These liquids may be used alone or in combination of two or more.

[0090] Alcohols: methanol (HSP value = 29.6), ethanol (HSP value = 26.5), 1-propanol (HSP value = 24.6), 2-propanol (IPA) (HSP value = 23.6), 1-butanol (HSP value = 23.2), 1-pentanol (HSP value = 21.7), 1-hexanol (HSP value = 21.2), benzyl alcohol (HSP value = 23.8), diethylene glycol (HSP value = 27.9), dipropylene glycol (HSP value = 26.4)

[0091] Hydrocarbons: benzene (HSP value = 18.5), toluene (HSP value = 18.2), styrene (HSP value = 19.1), hexane (HSP value = 14.9), cyclohexane (HSP value = 16.8), heptane (HSP value = 15.3), methylcyclohexane (HSP value = 16.0)

[0092] Ketones; acetone (HSP value = 19.9), methyl ethyl ketone (HSP value = 19.1)

[0093] Esters; Ethyl acetate (HSP value = 18.2)

[0094] Ethers; Tetrahydrofuran (HSP value = 19.5), Cyclopentyl methyl ether (HSP value = 17.8)

[0095] Amines; Aniline (HSP value = 23.7)

[0096] Nitriles; acetonitrile (HSP value = 24.4)

[0097] Carboxylic acids; acetic acid (HSP value = 21.4)

[0098] Terpenes; d-limonene (HSP value = 17.8)

[0099] As a liquid having a Hansen solubility parameter of 31 or less, a mixed liquid of a plurality of liquids having a Hansen solubility parameter of 31 or less as the above-mentioned single liquid and other liquids can also be used. In this case, as a mixed liquid, a mixed liquid can be used if m based on the above-mentioned formula (1) as a Hansen solubility parameter value is 31 or less. As a solvent that can be used as a mixed liquid by combining a plurality of liquids, for example, water (HSP value = 47.8) can be cited. For example, when water (HSP value = 47.8) and ethanol (HSP value = 26.5) are mixed in a volume fraction of water / ethanol = 20% / 80%, m = 30.76, and therefore, it can be used.

[0100] The liquid having a Hansen solubility parameter value of 31 or less preferably contains at least one selected from the group consisting of alcohols, hydrocarbons, ketones, esters, ethers, amines, nitriles, carboxylic acids, and terpenes.

[0101] From the viewpoint of the solubility of the basic compound, etc., the liquid having a Hansen solubility parameter value of 31 or less preferably necessarily contains an alcohol.

[0102] In the present invention, in order to distinguish from the alcohol used in step (II), the alcohol that can be contained in the liquid having a Hansen solubility parameter value of 31 or less used in step (I) may be referred to as "alcohol (A1)". Similarly, as described later, the alcohol used in step (II) may be referred to as "alcohol (A2)".

[0103] As alcohols (A1), any appropriate alcohols can be used within the range that does not impair the effect of the present invention. Such alcohols (A1) preferably include alcohols having 1 to 8 carbon atoms. As alcohols having 1 to 8 carbon atoms, not only primary alcohols but also secondary alcohols such as 2-propanol, propylene glycol monopropyl ether, and propylene glycol monoethyl ether, and tertiary alcohols such as tertiary butanol can be included. Alcohols (A1) may be only one kind or two or more kinds.

[0104] Examples of the alcohol having 1 to 8 carbon atoms include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 1-pentanol, 1-hexanol, cyclohexanol, benzyl alcohol, 1-heptanol, 1-octanol, and 2-ethylhexanol. Preferably, it contains a lower alcohol having 1 to 5 carbon atoms (representatively, at least one selected from methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 1-pentanol), and more preferably, it contains a lower alcohol having 1 to 4 carbon atoms (representatively, at least one selected from methanol, ethanol, 1-propanol, 2-propanol, and 1-butanol).

[0105] The acrylic adhesive used in step (I) has -COO-R 1 The base polymer contained in the acrylic adhesive composition used to form the acrylic adhesive used in step (I) has -COO-R 1 The structure of alcohol (A1) is R 21 In the case of -OH, the R 1 With the R 21 Can be the same or different.

[0106] The liquid having a Hansen solubility parameter value of 31 or less preferably contains an organic solvent other than alcohols (A1) in addition to alcohols (A1). Only one organic solvent other than alcohols (A1) may be used, or two or more organic solvents may be used in combination. The organic solvent other than alcohols (A1) is, for example, the above-mentioned ethers or the above-mentioned hydrocarbons, preferably at least one selected from toluene, cyclopentyl methyl ether, and tetrahydrofuran, and more preferably at least one selected from toluene and cyclopentyl methyl ether. If the liquid having a Hansen solubility parameter value of 31 or less is a mixed solvent of alcohols (A1) and an organic solvent (preferably at least one selected from ethers and hydrocarbons), for example, the permeability of the adhesive treatment liquid to the acrylic adhesive can be improved, and the manufacturing efficiency of the hydrophilic polymer can be improved.

[0107] When the liquid having a Hansen solubility parameter value of 31 or less contains alcohols (A1) and organic solvents other than alcohols (A1) (preferably at least one selected from ethers and hydrocarbons), the volume ratio of the organic solvent to the alcohol (A1) (organic solvent: alcohol) is preferably 10:90 to 99:1, more preferably 20:80 to 95:5, further preferably 30:70 to 90:10, particularly preferably 40:60 to 90:10, and most preferably 60:40 to 80:20. When the volume ratio of the organic solvent to the alcohol (A1) is within the above range, for example, the permeability of the adhesive treatment liquid to the acrylic adhesive can be further improved, and the production efficiency of the hydrophilic polymer can be stably improved.

[0108] As the basic compound, any appropriate basic compound can be adopted within the scope of not impairing the effect of the present invention. As such a basic compound, for example, hydroxides, carbonates, etc. of alkali metals or alkaline earth metals such as potassium hydroxide, sodium hydroxide, and calcium hydroxide, and metal alkoxides such as sodium methoxide, sodium ethoxide, and potassium tert-butoxide can be cited, preferably at least one selected from the group consisting of potassium hydroxide, sodium hydroxide, and sodium ethoxide.

[0109] The concentration of the alkaline compound in the adhesive treatment liquid is preferably 0.001 wt% to 20 wt%, more preferably 0.01 wt% to 10 wt%, further preferably 0.01 wt% to 8 wt%, particularly preferably 0.01 wt% to 5 wt%, and most preferably 0.5 wt% to 1.5 wt%. If the concentration of the alkaline compound in the adhesive treatment liquid is within the above range, a hydrophilic polymer can be more stably produced from an acrylic adhesive under mild conditions. When the concentration of the alkaline compound in the adhesive treatment liquid exceeds 20 wt%, there is a concern that the alkaline compound becomes less soluble in the treatment solvent (liquid having a Hansen solubility parameter value of 31 or less).

[0110] The binder treatment liquid may contain other additives. As other additives, any appropriate additives can be adopted within the range that does not impair the effects of the present invention.

[0111] <<1-2. Step (II)>>

[0112] The step (II) is a step of reacting the hydrophilic polymer obtained in the step (I) with the alcohol (A2) to produce a recycled acrylic polymer.

[0113] In step (II), any appropriate method can be adopted as a method for reacting the hydrophilic polymer obtained in step (I) with the alcohol (A2) within the range not impairing the effect of the present invention. As such a method, it is preferred to stir the hydrophilic polymer obtained in step (I) in the alcohol (A2) in the presence of any appropriate catalyst as required.

[0114] The ratio of the hydrophilic polymer to the alcohol (A2) obtained in step (I) can be any appropriate ratio within the range not impairing the effects of the present invention, depending on the type of the hydrophilic polymer to be used, the type of the alcohol (A2), etc. Such a ratio is preferably 1:0.5 to 1:50, more preferably 1:1 to 1:30, further preferably 1:3 to 1:20, and particularly preferably 1:5 to 1:10, for example, by weight.

[0115] As alcohols (A2), any appropriate alcohols can be used within the range that does not impair the effect of the present invention. Such alcohols (A2) may be monohydric alcohols, dihydric alcohols, or trihydric or higher alcohols. As such alcohols (A2), for example, alcohols having 1 to 12 carbon atoms may be mentioned, and as monohydric alcohols, for example, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, isobutanol, 2-butanol, tert-butanol, 1-pentanol, 3-methyl-1-butanol, 2-methyl-1-butanol, 2,2-dimethyl-1-propanol, 2-pentanol, 3-methyl-2-butanol, 3-pentanol, 2-methyl-2-butanol, 1-hexanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 4-methyl-1- Pentanol, 2-methyl-2-pentanol, 3-methyl-2-pentanol, 4-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2,3-dimethyl-1-butanol, 3,3-dimethyl-1-butanol, 2,3-dimethyl-2-butanol, 3,3-dimethyl-2-butanol, 2-ethyl-1-butanol, cyclohexanol, benzyl alcohol, 1-heptanol, 2-heptanol, 3-heptanol, 4-heptanol, 1-octanol, isooctyl alcohol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-dodecanol. Examples of diols include ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. Examples of trivalent or higher alcohols include glycerol and polyvinyl alcohol. In terms of further exhibiting the effects of the present invention, methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, and 2-ethylhexanol are preferred. The alcohol (A2) may be one kind or two or more kinds.

[0116] Any appropriate catalyst can be used as the catalyst within the range not impairing the effects of the present invention. Examples of such catalysts include sulfuric acid, hydrochloric acid, nitric acid, p-toluenesulfonic acid, boron trifluoride, trifluoroacetic acid, and heavy metal salt catalysts.

[0117] As the amount of the catalyst, any appropriate amount can be adopted within the range that does not impair the effect of the present invention. As such an amount, in terms of further reflecting the effect of the present invention, it is preferably 0.01 equivalent to 5 equivalents, more preferably 0.05 equivalent to 3 equivalents, further preferably 0.1 equivalent to 2 equivalents, and particularly preferably 0.15 equivalent to 1 equivalent relative to 1 equivalent of the hydrophilic polymer obtained in step (I). It should be noted that when the hydrophilic polymer is carboxylated with an alkali metal or the like, in addition to the acid used as a catalyst for esterification, any appropriate acid in an amount required for neutralization can be added.

[0118] As a stirring method, any appropriate stirring method can be appropriately adopted within a range that does not impair the effects of the present invention. As for the stirring time, any appropriate stirring time can be appropriately adopted within a range that does not impair the effects of the present invention.

[0119] As the reaction temperature in step (II), any appropriate reaction temperature can be suitably adopted within the range that does not impair the effect of the present invention. As such a reaction temperature, in terms of further reflecting the effect of the present invention, it is preferably 50°C or more, more preferably 70°C or more, further preferably 80°C or more, and particularly preferably 90°C or more, and the upper limit is preferably 350°C or less, more preferably 300°C or less, further preferably 275°C or less, and particularly preferably 250°C or less.

[0120] During the reaction in step (II), other additives may be used. Any appropriate other additives may be used as long as the effects of the present invention are not impaired.

[0121] According to step (II), it is presumed that the carboxylic acid part is esterified by the Fischer esterification reaction. Thus, a recycled acrylic polymer derived from an acrylic adhesive is formed. Here, the "recycled acrylic polymer derived from an acrylic adhesive" refers to an acrylic polymer having a structure derived from a base polymer used in the formation of an acrylic adhesive, and specifically, for example, refers to an acrylic polymer having a molecular weight derived from an acrylic adhesive, a side chain that does not contribute to a hydrolysis reaction and an esterification reaction, and the like.

[0122] The weight average molecular weight of the recycled acrylic polymer obtained in step (II) is preferably 100,000 to 3,000,000, more preferably 150,000 to 2,000,000, further preferably 200,000 to 1,500,000, and particularly preferably 250,000 to 1,000,000.

[0123] The Tg (glass transition temperature) of the recycled acrylic polymer obtained in step (II) is preferably -100°C to 30°C, more preferably -95°C to 20°C, further preferably -90°C to 10°C, particularly preferably -80°C to 0°C.

[0124] The acrylic adhesive used in step (I) has -COO-R 1 The base polymer contained in the acrylic adhesive composition used to form the acrylic adhesive used in step (I) has -COO-R 1 The structure of alcohol (A2) is R 22 In the case of -OH, the R 1 With the R 22 They can be the same or different. In the above case, R 1 With R22 If they are the same, the recycled acrylic polymer obtained in step (II) can have the same ester structure as the base polymer contained in the acrylic adhesive composition used to form the acrylic adhesive used in step (I). 1 With R 22 If they are different, the recycled acrylic polymer obtained in step (II) has an ester structure different from that of the base polymer contained in the acrylic pressure-sensitive adhesive composition used to form the acrylic pressure-sensitive adhesive used in step (I).

[0125] The recycled acrylic polymer obtained in step (II) typically contains a structural unit (1) represented by the following formula and a structural unit (2) represented by the following formula.

[0126] [Chemistry 1]

[0127]

[0128] (Where R 3 represents a hydrogen atom or a methyl group. 4 represents an alkyl group having 1 to 12 carbon atoms. M represents a hydrogen atom or a cation.

[0129] The recycled acrylic polymer obtained in step (II) typically contains a plurality of structural units (1) and structural units (2). In the molecular chain of the recycled acrylic polymer obtained in step (II), structural units (1) and structural units (2) are typically randomly arranged.

[0130] In the structural units (1) and (2), R 3 represents a hydrogen atom or a methyl group, preferably a hydrogen atom. 3 They may be the same as or different from each other. In the structural units (1) and (2), R 1 They may be the same as or different from each other. The recycled acrylic polymer obtained in step (II) has the structural unit (1), so that the glass transition temperature of the recycled acrylic polymer is lowered and the flexibility at room temperature is improved. The recycled acrylic polymer obtained in step (II) has the structural unit (2), so that the recycled acrylic polymer is soluble in water. The recycled acrylic polymer obtained in step (II) has the structural units (1) and (2), so that it can become a suitable raw material for the base polymer of the adhesive.

[0131] In the structural unit (1), as R 4The alkyl group represented by is preferably an alkyl group having 1 to 10 carbon atoms, more preferably a methyl group, an ethyl group, an n-butyl group and a 2-ethylhexyl group. 4 They may be the same as or different from each other.

[0132] In the structural unit (2), the cation represented by M is preferably an alkali metal cation or an alkaline earth metal cation, more preferably an alkali metal cation, and still more preferably a potassium cation or a sodium cation. In a plurality of structural units (2), M may be the same as or different from each other.

[0133] The content of the structural unit (1) in the recycled acrylic polymer obtained in step (II) is preferably 1% by weight or more, more preferably 3% by weight or more, further preferably 5% by weight or more, particularly preferably 10% by weight or more, and the upper limit is preferably 95% by weight or less, more preferably 90% by weight or less, further preferably 85% by weight or less, particularly preferably 80% by weight or less.

[0134] The content of the structural unit (2) in the recycled acrylic polymer obtained in step (II) is preferably 5% by weight or more, more preferably 10% by weight or more, further preferably 15% by weight or more, particularly preferably 20% by weight or more, and the upper limit is preferably 95% by weight or less, more preferably 90% by weight or less, further preferably 87% by weight or less, particularly preferably 85% by weight or less.

[0135] The content ratio of structural unit (1) relative to the sum of structural unit (1) and structural unit (2) is preferably 5% by weight or more, more preferably 7% by weight or more, further preferably 10% by weight or more, and the upper limit is preferably 95% by weight or less, more preferably 90% by weight or less, further preferably 93% by weight or less, and particularly preferably 90% by weight or less.

[0136] The content ratio of the structural unit can be measured by, for example, FT-IR method, NMR method, or titration method.

[0137] <<1-3. Step (III)>>

[0138] The method for producing a recycled acrylic adhesive according to an embodiment of the present invention may include a step (III) of separating the acrylic adhesive from the adhesive tape. The adhesive tape used in the step (III) may be a waste adhesive tape (sometimes referred to as "waste adhesive tape"). If such a step (III) is included, the recycled acrylic adhesive can be produced using waste adhesive tapes generated in large quantities at a manufacturing site or the like as a raw material.

[0139] The acrylic pressure-sensitive adhesive separated in step (III) can be used in step (I). Therefore, it is preferred to include step (III) before step (I).

[0140] In step (III), the acrylic adhesive is separated from any appropriate adhesive tape. Representative examples of such adhesive tapes include adhesive tapes without a substrate and adhesive tapes with a substrate (representatively, an adhesive tape having an adhesive layer composed of an acrylic adhesive and a substrate).

[0141] As a method for separating the acrylic pressure-sensitive adhesive from the pressure-sensitive adhesive tape, any appropriate method may be adopted within a range that does not impair the effects of the present invention.

[0142] When the adhesive tape is an adhesive tape with a substrate (representatively, an adhesive tape having an adhesive layer composed of an acrylic adhesive and a substrate), a preferred embodiment of a method for separating the acrylic adhesive from the adhesive tape includes a method of grinding the surface of the adhesive layer possessed by the adhesive tape to separate the acrylic adhesive constituting the adhesive layer from the substrate layer.

[0143] As a method for grinding the surface of the adhesive layer of the adhesive tape, any appropriate grinding method can be adopted within the scope that does not impair the effect of the present invention. As such a grinding method, for example, a method using a belt sander equipped with a grinding belt can be cited. That is, the grinding belt of the belt sander equipped with a grinding belt is brought into contact with the surface of the adhesive layer of the adhesive tape. In this case, it can be an embodiment in which the adhesive layer of the adhesive tape is pressed onto the grinding belt, it can be an embodiment in which the grinding belt is pressed onto the adhesive layer of the adhesive tape, and it can also be another embodiment in which the grinding belt is brought into contact with the surface of the adhesive layer of the adhesive tape.

[0144] 《1-4. Step (IV)》

[0145] The recycled acrylic polymer obtained in step (II) may be used directly as a recycled acrylic adhesive, or may react with a crosslinking agent to become a recycled acrylic adhesive having a crosslinked structure. That is, the method for producing a recycled acrylic adhesive according to an embodiment of the present invention may include the following step (IV): reacting the recycled acrylic polymer obtained in step (II) with a crosslinking agent. Preferably, step (IV) may be included after step (II).

[0146] Step (IV) Typically, the recycled acrylic adhesive composition containing the recycled acrylic polymer and the crosslinking agent is reacted with the recycled acrylic polymer and the crosslinking agent to obtain a recycled acrylic adhesive having a crosslinked structure.

[0147] By using a crosslinking agent, it is possible to impart appropriate cohesive force to the recycled acrylic adhesive. The crosslinking agent may be contained in the recycled acrylic adhesive in a form after a crosslinking reaction, a form before a crosslinking reaction, a form partially crosslinked, a form intermediate therebetween, or a composite form. The crosslinking agent is typically contained in the recycled acrylic adhesive in a form after a crosslinking reaction.

[0148] The content ratio of the crosslinking agent in the acrylic pressure-sensitive adhesive composition is preferably 0.005 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, further preferably 0.01 to 3 parts by mass, further preferably 0.01 to 1 part by mass, particularly preferably 0.01 to 0.5 parts by mass, and most preferably 0.01 to 0.2 parts by mass, based on 100 parts by mass of the recycled acrylic polymer.

[0149] As the crosslinking agent, for example, there can be mentioned: isocyanate crosslinking agents, epoxy crosslinking agents, silicone crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, silane crosslinking agents, alkyl etherified melamine crosslinking agents, metal chelate crosslinking agents, peroxide and other crosslinking agents. In terms of further reflecting the effects of the present invention, isocyanate crosslinking agents and epoxy crosslinking agents are preferred, and isocyanate crosslinking agents are more preferred.

[0150] Isocyanate crosslinking agents can be compounds having two or more isocyanate groups in one molecule (including isocyanate regenerating polar groups whose isocyanate groups are temporarily protected by blocking agents or polymerization). Examples of isocyanate crosslinking agents include aromatic isocyanates such as toluene diisocyanate and xylene diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate.

[0151] Examples of the isocyanate crosslinking agent include: lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylene diisocyanate, and polymethylene polyphenyl polyisocyanate; trimethylolpropane / toluene diisocyanate adducts (e.g., Coronate L manufactured by Nippon Polyurethane Industry Co., Ltd. or Tosoh Corporation, Takenate L manufactured by Mitsui Chemicals, Inc.) Isocyanate adducts such as trimethylolpropane / hexamethylene diisocyanate adduct (e.g., trade name “Takenate D101E” manufactured by Nippon Polyurethane Industry Co., Ltd. or Tosoh Corporation), isocyanurate of hexamethylene diisocyanate (e.g., trade name “Coronate HX” manufactured by Nippon Polyurethane Industry Co., Ltd. or Tosoh Corporation); trimethylolpropane / xylene diisocyanate adduct (e.g., trade name “Takenate D110N” manufactured by Mitsui Chemicals, Inc., trade name “Takenate D120N” manufactured by Mitsui Chemicals, Inc.), trimethylolpropane / isophorone diisocyanate adduct (e.g., trade name “Takenate D140N” manufactured by Mitsui Chemicals, Inc.), trimethylolpropane / hexamethylene diisocyanate adduct (e.g., trade name “Takenate D160N” manufactured by Mitsui Chemicals, Inc.), and isocyanurate of hexamethylene diisocyanate (e.g., trade name “Takenate D170N” manufactured by Mitsui Chemicals, Inc.). D160N”); polyether polyisocyanate, polyester polyisocyanate, and adducts of these with various polyols; polyisocyanates multifunctionalized with isocyanurate bonds, biuret bonds, allophanate bonds, etc.

[0152] As the epoxy crosslinking agent, a multifunctional epoxy compound having two or more epoxy groups in one molecule can be used. Examples of the epoxy crosslinking agent include: N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polycondensate, Water glyceryl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl isocyanurate-tri(2-hydroxyethyl)ester, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resin having two or more epoxy groups in the molecule. Commercially available products of epoxy crosslinking agents include, for example, trade names "TETRAD C" and "TETRAD X" (manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0153] The acrylic adhesive composition may contain various additives commonly used in the adhesive field, such as catalysts, solvents, tackifiers, leveling agents, crosslinking aids, plasticizers, softeners, fillers, antistatic agents, antioxidants, ultraviolet absorbers, antioxidants, and light stabilizers, as needed. For such various additives, conventionally known substances may be used according to conventional methods.

[0154] For the method of reacting the recycled acrylic polymer with the crosslinking agent as an acrylic adhesive composition containing a recycled acrylic polymer and a crosslinking agent, any appropriate method can be adopted within the scope that does not damage the effect of the present invention. As such a method, for example, the following method can be cited: the acrylic adhesive composition is coated on any appropriate substrate, heated / dried as needed, cured as needed, a crosslinking reaction is caused on the substrate, and the recycled acrylic adhesive is formed into a sheet. As such a coating means, any appropriate means can be adopted within the scope that does not damage the effect of the present invention. As such a coating means, for example, a gravure roll coater, a reverse roll coater, a licking roll coater, a dip roll coater, a rod coater, a blade coater, an air knife coater, a spray coater, a comma coater, a direct coater, and a roller brush coater. The heating / drying of the acrylic adhesive composition can adopt any appropriate means within the scope that does not damage the effect of the present invention. As such a heating / drying means, for example, heating to about 60°C to 180°C can be cited. The acrylic adhesive composition can be cured by any appropriate means within the range that does not impair the effects of the present invention, such as ultraviolet irradiation, laser beam irradiation, α-ray irradiation, β-ray irradiation, γ-ray irradiation, X-ray irradiation, and electron beam irradiation.

[0155] <<<<2. Reuse of acrylic adhesive tape>>>>

[0156] The recycled acrylic pressure-sensitive adhesive tape according to the embodiment of the present invention includes the recycled acrylic pressure-sensitive adhesive obtained by the method for producing a recycled acrylic pressure-sensitive adhesive according to the embodiment of the present invention and a substrate.

[0157] In view of functioning as a pressure-sensitive adhesive tape, the thickness of the substrate is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, further preferably 10 μm to 100 μm, particularly preferably 15 μm to 80 μm, and most preferably 20 μm to 60 μm.

[0158] As the material of the substrate, any appropriate material can be adopted within the range that does not impair the effects of the present invention. As a material of such a substrate, a resin material can be typically mentioned.

[0159] Examples of resin materials used as substrate materials include acrylic resins such as polyimide (PI), polyetheretherketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resins, and cyclic olefin-based polymers.

[0160] The recycled acrylic pressure-sensitive adhesive tape of the embodiment of the present invention can be manufactured by any appropriate method within the range that does not impair the effects of the present invention. As such a manufacturing method, for example, the following method can be cited:

[0161] Method (1), forming a recycled acrylic adhesive on a substrate;

[0162] Method (2), transferring the recycled acrylic adhesive formed on the release liner to the substrate;

[0163] Method (3) is to laminate and reuse an acrylic adhesive on a substrate.

[0164] The recycled acrylic pressure-sensitive adhesive contained in the recycled acrylic pressure-sensitive adhesive tape according to the embodiment of the present invention constitutes a pressure-sensitive adhesive layer on the substrate.

[0165] In view of the function as a pressure-sensitive adhesive tape, the thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 250 μm, more preferably 2 μm to 150 μm, further preferably 3 μm to 100 μm, and particularly preferably 5 μm to 50 μm.

[0166] The recycled acrylic pressure-sensitive adhesive tape according to the embodiment of the present invention may include any appropriate release liner on the surface of the pressure-sensitive adhesive layer opposite to the substrate layer for protection until use.

[0167] Examples of the release liner include: a release liner having a surface treated with silicone such as paper or plastic film (liner substrate); a release liner having a surface laminated with a polyolefin resin such as paper or plastic film (liner substrate); and the like. Examples of the plastic film used as the liner substrate include: polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, ethylene-vinyl acetate copolymer film, and the like.

[0168] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, further preferably 5 μm to 400 μm, and particularly preferably 10 μm to 300 μm.

[0169] Example

[0170] Hereinafter, the present invention will be specifically described based on the examples, but the present invention is not limited to these examples. It should be noted that the test and evaluation methods in the examples are as follows. It should be noted that when "parts" are recorded, they refer to "parts by weight" unless otherwise specified, and when "%" is recorded, it refers to "% by weight" unless otherwise specified. In addition, "room temperature" refers to 25°C.

[0171] <Measurement of Tg>

[0172] DSC measurement was performed using a measuring device "DSC2500" manufactured by TA Instruments, and Tg was confirmed.

[0173] [Example 1]

[0174] A 5 cm wide acrylic adhesive tape (manufactured by Nitto Denko Corporation, trade name "No. 31B") was conveyed while removing the release liner, and the abrasive tape of a belt sander (BE-3210, manufactured by RYOBI) equipped with an abrasive tape (grain size = #100, manufactured by Makita Corporation) was pressed against the exposed adhesive layer at a belt speed of 5.8 m / sec with a tension of 5 N, thereby separating the acrylic adhesive (1) constituting the adhesive layer.

[0175] The structure of the acrylic pressure-sensitive adhesive (1) was analyzed by NMR (AVANCE III-600 with cryo probe, manufactured by Bruker Biospin), and it was found to contain a -COOC4H9 group. The Tg of the base polymer was -40°C.

[0176] Potassium hydroxide was added to a mixed solution of methylcyclohexane / 1-butanol = 70 / 30 (volume ratio) (Hansen solubility parameter value of the mixed solution = 17) to a concentration of 2 wt % to prepare a binder treatment solution (1).

[0177] 500 g of the adhesive treatment liquid (1) was mixed with 50 g of the acrylic adhesive (1), and the mixture was stirred at 50° C. for 10 hours. The precipitated solid was washed with ethyl acetate and dried at 130° C. for 1 hour to obtain a hydrophilic polymer (1).

[0178] The Tg of the hydrophilic polymer (1) is 115°C.

[0179] When the structure of the hydrophilic polymer (1) was analyzed by NMR (AVANCE III-600 with cryo probe, manufactured by Bruker Biospin), it was found that it had a -COOC4H9 group and a -COOK group.

[0180] 20 g of the obtained hydrophilic polymer (1) was mixed with 0.25 equivalent of sulfuric acid and 200 g of 1-butanol relative to the hydrophilic polymer (1), and stirred at 110° C. for 9 hours to obtain a supernatant in which the polymer component was dissolved in 1-butanol and a neutralized product of the carboxylate.

[0181] The supernatant obtained by dissolving the polymer component in 1-butanol was collected and added dropwise to water to extract the polymer component. The polymer component was washed with water and tetrahydrofuran until the pH of the washing liquid reached 5 or more, and the obtained polymer component was dried at 130° C. for 1 hour to obtain a recycled acrylic polymer (1).

[0182] The Tg of the recycled acrylic polymer (1) was -46°C.

[0183] When the structure of the recycled acrylic polymer (1) was analyzed by NMR (AVANCE III-600 with cryo probe, manufactured by Bruker Biospin), it was found that it had a -COOC4H9 group and a -COOH group.

[0184] The recycled acrylic polymer (1) can be used as a recycled acrylic adhesive as it is.

[0185] [Example 2]

[0186] Potassium hydroxide was added to a mixed solution of cyclopentyl methyl ether / methanol = 70 / 30 (volume ratio) (Hansen solubility parameter value of the mixed solution = 20) so as to have a concentration of 1.3 wt % to prepare a binder treatment solution (2).

[0187] 500 g of the binder treatment solution (2) was mixed with 50 g of the acrylic binder (1) separated in Example 1, and the mixture was stirred at 50° C. for 10 hours. The precipitated solid component was washed with ethyl acetate and dried at 130° C. for 1 hour to obtain a hydrophilic polymer (2).

[0188] The Tg of the hydrophilic polymer (2) is 105°C.

[0189] When the structure of the hydrophilic polymer (2) was analyzed by NMR (AVANCE III-600 with cryo probe, manufactured by Bruker Biospin), it was found that it had a -COOC4H9 group, a -COOCH3 group, and a -COOK group.

[0190] 20 g of the obtained hydrophilic polymer (2) was mixed with 0.25 equivalents of sulfuric acid and 200 g of 1-butanol relative to the hydrophilic polymer (2), and stirred at 110° C. for 6 hours to obtain a supernatant in which the polymer component was dissolved in 1-butanol and a neutralized product of the carboxylate.

[0191] The supernatant obtained by dissolving the polymer component in 1-butanol was collected and added dropwise to water to extract the polymer component. The polymer component was washed with water and tetrahydrofuran until the pH of the washing liquid reached 5 or more, and the obtained polymer component was dried at 130° C. for 1 hour to obtain a recycled acrylic polymer (2).

[0192] The Tg of the recycled acrylic polymer (2) was -22°C.

[0193] When the structure of the recycled acrylic polymer (2) was analyzed by NMR (AVANCE III-600 with cryo probe, manufactured by Bruker Biospin), it was found that it had a -COOC4H9 group, a -COOCH3 group, and a -COOH group.

[0194] The recycled acrylic polymer (2) can be used as a recycled acrylic adhesive as it is.

[0195] [Example 3]

[0196] 100 parts by weight of the recycled acrylic polymer (1) obtained in Example 1 and 3 parts by weight of a TDI-based isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "Coronate L") were blended to prepare an acrylic pressure-sensitive adhesive composition (1).

[0197] A polyethylene terephthalate film having a thickness of 38 μm (manufactured by Mitsubishi Chemical Corporation, trade name "Diafoil") was used as a substrate, and an acrylic adhesive composition (1) was applied to the substrate so as to have a thickness of 25 μm after drying. The film was dried at a drying temperature of 115° C. and a drying time of 2 minutes to produce a reusable acrylic adhesive tape (1).

[0198] [Example 4]

[0199] 100 parts by weight of the recycled acrylic polymer (2) obtained in Example 2 and 3 parts by weight of a TDI-based isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "Coronate L") were blended to prepare an acrylic pressure-sensitive adhesive composition (2).

[0200] A polyethylene terephthalate film having a thickness of 38 μm (manufactured by Mitsubishi Chemical Corporation, trade name "Diafoil") was used as a substrate, and an acrylic adhesive composition (2) was applied to the substrate so that the thickness after drying would be 25 μm. The film was dried at a drying temperature of 115° C. and a drying time of 2 minutes to produce a reusable acrylic adhesive tape (2).

[0201] 〔evaluate〕

[0202] The recycled acrylic pressure-sensitive adhesive tape (1) obtained in Example 3, the recycled acrylic pressure-sensitive adhesive tape (2) obtained in Example 4, and the acrylic pressure-sensitive adhesive tape of Reference Example 1 (manufactured by Nitto Denko Corporation, trade name "No. 31B") were used, all aligned to a width of 25 mm, attached to an adherend, and attached by reciprocating once with a 2 kg hand roller to obtain evaluation samples.

[0203] After the obtained evaluation sample is stored at room temperature (23°C) for 30 minutes, it is measured with a tensile testing machine. The trade name "Autograph AGX-V" manufactured by Shimadzu Corporation is used as a tensile testing machine. After the evaluation sample is installed on the tensile testing machine, the tensile test is started. The conditions of the tensile test are set as peeling angle: 180 degrees, peeling speed (tensile speed): 300 mm / min, and the load when peeling the adhesive tape from the adherend is measured, and the average load at this time is taken as the adhesive force

[0204] SUS board, PC (polycarbonate) board, PS (polystyrene) board, PE (polyethylene) board, and acrylic board are used as the adherend.

[0205] The results are shown in Table 1.

[0206] [Table 1]

[0207]

[0208] Industrial Applicability

[0209] The method for producing a recycled acrylic pressure-sensitive adhesive of the present invention can be effectively used for recycling a large amount of pressure-sensitive adhesive tape waste generated at, for example, a production site of electronic components or optical components.

Claims

1. A method for producing a recycled acrylic adhesive, comprising the following steps: Step (I), reacting an acrylic adhesive with a liquid having a Hansen solubility parameter value of 31 or less and a basic compound to produce a hydrophilic polymer; and, In step (II), the hydrophilic polymer is reacted with an alcohol (A2) to produce a recycled acrylic polymer.

2. The method for producing a recycled acrylic adhesive according to claim 1, wherein: The liquid having a Hansen solubility parameter value of 31 or less includes at least one selected from the group consisting of alcohols (A1), hydrocarbons, ketones, esters, ethers, amines, nitriles, carboxylic acids, and terpenes.

3. The method for producing a recycled acrylic adhesive according to claim 2, wherein: The liquid having a Hansen solubility parameter value of 31 or less must contain the alcohol (A1).

4. The method for producing a recycled acrylic adhesive according to claim 3, wherein: The alcohols (A1) include alcohols having 1 to 8 carbon atoms.

5. The method for producing a recycled acrylic adhesive according to claim 2, wherein: The acrylic adhesive has -COO-R 1 The alcohol (A1) has a structure of R 21 -OH, the R 1 With the R 21 same.

6. The method for producing a recycled acrylic adhesive according to claim 2, wherein: The acrylic adhesive has -COO-R 1 The alcohol (A1) has a structure of R 21 -OH, the R 1 With the R 21 different.

7. The method for producing a recycled acrylic adhesive according to claim 1, wherein: The acrylic adhesive has -COO-R 1 The alcohol (A2) has a structure of R 22 -OH, the R 1 With the R 22 same.

8. The method for producing a recycled acrylic adhesive according to claim 1, wherein: The acrylic adhesive has -COO-R 1 The alcohol (A2) has a structure of R 22 -OH, the R 1 With the R 22 different. 9 . The method for producing a recycled acrylic adhesive according to claim 1 , comprising the step (III) of separating the acrylic adhesive from an adhesive tape having the acrylic adhesive. 10 . The method for producing a recycled acrylic adhesive according to claim 1 , comprising the step (IV) of reacting the recycled acrylic polymer with a crosslinking agent. 11 . A recycled acrylic pressure-sensitive adhesive tape comprising: a recycled acrylic pressure-sensitive adhesive obtained by the production method according to claim 1 ; and a substrate.

Citation Information

Patent Citations

  • Acrylic adhesives and its production method

    JP2002069411A

  • Double-sided adhesive tape

    JP2021175796A